Feasibility of Using ISO Shipping Container to Build Low Cost House in Malaysia - King Hui Wong, Edric; Siang Tan, Cher; Chie Hui Ling, Philip (International Journal of Engineering and Technology, 2018)
The idea of shipping container house is no longer a revolutionized to western country but in Asia country particularly in Malaysia it is relatively new. The idea of container house is relatively new and there is no clear sign of how far does Malaysian citizen can accept this idea. There is no indicator of what are the expectations from Malaysian citizen about the container house. This research serves as basic references for both government and private sector to the future property industry development of shipping container house as well as shipping container non-residential building in Malaysia to pursue Malaysiaâ€™s unity, economic and national integration. The purpose of this study is to test the feasibility of using ISO shipping container to build low cost house. Four set of questionnaires are prepared to assess the opinion of respondents about the acceptance of shipping container house. The result obtained is that the acceptance level of the idea to live inside a container house is only 45% but the acceptance level of using shipping container as means of storage, office, and business development is highly acceptable by Malaysian citizen.Â Â